The toxicology of carbon nanotubes - Donaldson, Kenneth (Toxicologist) (Cambridge University Press, 2012)
"The widespread and increasing use of carbon nanotubes in scientific and engineering research and their incorporation into manufactured goods has urged an assessment of the risks and hazards associated with exposure to them. The field of nanotoxicology studies the toxicology of nanoparticles such as carbon nanotubes and has become a major growth area aimed towards risk assessment of nanoparticles. Compiled by a team of leading experts at the forefront of research, this is the first book dedicated to the toxicology of carbon nanotubes. It provides state-of-the-science information on how and why they are so potentially dangerous if breathed in, including their similarities to asbestos. The book examines various aspects of carbon nanotubes, from their manufacture and aerodynamic behaviour to their effects at molecular level in the lungs. It is invaluable to the many groups involved with research in this area, as well as to regulators and risk assessors."--